Anagogicis... excessibus: a philological addendum on the religious phenemonology of Frans Titelmans - Andersson, Daniel Christopher (Verbum – Analecta Neolatina, 2009)
The usage of the term anagogicis excessibus in the Low Countries philosopher Frans Titlemans' 1530 compend of natural philosophy Libri duodecim de consyderatione rerum naturalium shows a strongly religious underpinning to his scientific thought. It is the purpose of this article to draw attention to the phrase, and to prove the Bonaventuran religious background in scriptural hermeneutics. This detail points to an important aspect of the Franciscan natural philosophical tradition.